The Counter-Memory, the Antisocial and the Counter-image in the Last Two Juan Gabriel Vásquez Novels “The Sound of Things Falling” (2011) and “The Reputations” (2013) (2015)
Juan Gabriel Vásquez’s narrative approaches the 20th century political Colombian history. He tracks the latent past that he transforms into a vehement desire of prominent figures to forget the painful past, and abolish what they have lived. This characteristic is defined as counter memory, a hermeneutic term. The counter-image corresponds to the different negative aspects that people show. Both novels in this study, “The sound of things falling” and “The reputations” become two possible interpretations of the official history. The author studies in depth the past and the need to understand it. As a consequence, the characters find themselves in unexpected contexts in diverse situations.